Testing The Suitability of The Indonesian and Vietnamese Baselines under UNCLOS - Widodo, Muhamad (Padjadjaran Journal of International Law, 2024)
The method for drawing baselines for the determination of maritime areas has been regulated in UNCLOS through three legal baselines, namely Normal Baselines, Straight Baselines, and Archipelagic Baselines. Respectively these approaches have been modified to suit the typical geographic features of a coastal state. However, the determination of baselines by several states is inconsistent with applicable regulations and has the potential to cause disputes with neighboring states. Indonesia has established straight baselines based on archipelago theory, on the other hand, Vietnam has established straight baselines. This article tries to identify the suitability of determining the baseline from Indonesia and Vietnam based on UNCLOS provisions and concludes that there was a violation of Article 7 of UNCLOS by Vietnam.